2010
DOI: 10.1021/ja102744b
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Site-Specific 13C Spin−Lattice Relaxation in a Crystalline Protein

Abstract: We demonstrate that it is possible to record site-specific spin-lattice relaxation rates for the majority of (13)C sites in uniformly (13)C and (15)N labeled solid proteins as a result of the slowing down of proton-driven spin diffusion at sample spinning frequencies > or = 60 kHz, thus providing a series of new experimental probes for characterizing molecular dynamics in solid proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
186
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(195 citation statements)
references
References 26 publications
9
186
0
Order By: Relevance
“…S5). We probed polyQ side-chain motion via 15 N R 1 , 15 N R 1ρ , 13 C R 1 , and 13 C R 1ρ relaxation measurements, in part enabled by ultrafast MAS (36,37) (Fig. 3 G-I and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S5). We probed polyQ side-chain motion via 15 N R 1 , 15 N R 1ρ , 13 C R 1 , and 13 C R 1ρ relaxation measurements, in part enabled by ultrafast MAS (36,37) (Fig. 3 G-I and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for protonated alanine spinning below 20 kHz MAS, the 13 C relaxation rate constants of carbonyl, C α and methyl-13 C are essentially the same (about 1.5 to 2.5 s −1 ) [102]. When increasing the MAS frequency to 60 kHz the respective rates differ between each other by almost a factor 50, showing that spin diffusion is strongly reduced (although the rates still may not necessarily reflect the actual relaxation rate constants).…”
Section: Longitudinal Relaxation Parameters In Solid-state Nmrmentioning
confidence: 98%
“…When increasing the MAS frequency to 60 kHz the respective rates differ between each other by almost a factor 50, showing that spin diffusion is strongly reduced (although the rates still may not necessarily reflect the actual relaxation rate constants). It was proposed that ~60 kHz MAS frequency may suffice to provide site-specific R 1 relaxation rate constants [102]. However, a recent study challenged this view, and showed that for 13 C α sites fast MAS alone is insufficient, and even deuteration and >50 kHz MAS (in a fully 13 Clabeled protein) is insufficient to suppress the effect of spin diffusion on 13 C α R 1 relaxationrate constants.…”
Section: Longitudinal Relaxation Parameters In Solid-state Nmrmentioning
confidence: 99%
“…1 103 resonances were resolved in the CP-HSQC, indicating that the CP-HSQC experiment is an efficient detection block for 15 N or 13 C relaxation measurements. Thus, the 15 N-1 H CP-HSQC dipolar correlation module was combined with a 15 N inversion-recovery block (30,31), 15 N spin-lock (32,33), or additional 13 C-15 N specific transfers (34) and 13 C inversion-recovery (35) into a new set of extremely sensitive and resolved experiments. Pulse schemes are shown in Fig.…”
mentioning
confidence: 99%
“…This is particularly relevant in the site-specific measurement of the 15 N R 1ρ and 13 CO R 1 , which are both particularly susceptible to residual effects. It has been shown that these parameters can be accurately measured under MAS by using MAS frequencies >40 kHz and a spin-lock nutation frequency >10 kHz (31,33,35).…”
mentioning
confidence: 99%